2016
DOI: 10.1007/s12192-016-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts anti-inflammatory and antioxidative properties in 1-methyl-4-phenylpyridinium ion (MPP+)-stimulated mesencephalic astrocytes by interference with TLR4 and downstream signaling pathway

Abstract: Neuroinflammation is closely associated with the pathophysiology of neurodegenerative diseases including Parkinson's disease (PD). Recent evidence indicates that astrocytes also play pro-inflammatory roles in the central nervous system (CNS) by activation with toll-like receptor (TLR) ligands. Therefore, targeting anti-inflammation may provide a promising therapeutic strategy for PD. Curcumin, a polyphenolic compound isolated from Curcuma longa root, has been commonly used for the treatment of neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 48 publications
2
38
0
2
Order By: Relevance
“…Recent reports suggest that due to curcumin's ability to reduce Beta-amyloid plaques, delay degradation of neurons, as well as decrease inflammatory microglia responses, the overall memory in patients with AD results significantly improved [153,154].…”
Section: The Positive Effects Of Cur Are Not Limited To Improve Neuromentioning
confidence: 99%
“…Recent reports suggest that due to curcumin's ability to reduce Beta-amyloid plaques, delay degradation of neurons, as well as decrease inflammatory microglia responses, the overall memory in patients with AD results significantly improved [153,154].…”
Section: The Positive Effects Of Cur Are Not Limited To Improve Neuromentioning
confidence: 99%
“…24) Recent studies have also revealed that curcumin has protective effects against PD-related neurotoxicants, such as MPP + , rotenone, salsolinol, and 6-hydroxydopamine (6-OHDA) in neurons and/or glial cells. 14,15,25) However, the effects of curcumin against Mn toxicity in microglia have not been reported. Therefore, this study investigated that curcumin can suppress Mn-induced cytotoxicity in BV-2 microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…12,13) Further, curcumin effectively protected neurons and/or glial cells against various neurotoxins. 14,15) However, the effect of curcumin against Mn-induced cell death has not been studied. In the present study, we examined the possible protective effect of curcumin against Mn-induced BV-2 microglial cell damage.…”
mentioning
confidence: 99%
“…A study of van de Merwe et al proposed that curcumin (Cur) protected against PD injury in a PINK1-knockdown cell model [2]. Cur, or diferuloylmethane, is a natural ingredient extracted from Curcuma longa rhizome [5,6]. It has attracted great interest for its numerous pharmacological properties such as anti-inflammation, antioxidant, anti-tumor and anti-nerve degeneration [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Liu et al demonstrated that Cur was protective in PC12 cell models of PD stimulated by A53T α-synuclein [9]. Yu et al investigated via an MPP + -introduced PD model suggested that the anti-inflammatory and anti-oxidative roles of Cur were by interacting with TLR4 and its downstream effectors [5]. Cui et al emphasized its mitigation on PD dopaminergic neural damage, of which increased tyrosine hydroxylase (TH) activity was included as a parameter [8].…”
Section: Introductionmentioning
confidence: 99%